2016
DOI: 10.1097/mpa.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Small Interfering RNA Targeting Human Nestin Inhibits Pancreatic Cancer Cell Proliferation and Metastasis

Abstract: Nestin plays a key role in pancreatic cancer cell metastasis and stemness and that administration of nestin siRNA may offer a novel therapeutic strategy for pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
3
28
0
Order By: Relevance
“…In this study, we used serum-containing medium because PANC-1 cells most rapidly form large spheres under these conditions. The spheres generated from these cells expressed high mRNA levels of CSC markers, suggesting that they contain CSCs (7,13,(17)(18)(19). A previous study showed that PANC-1 cells grown in a serum-containing medium formed clusters that were heterogeneous for dye efflux, while cells grown in the serum-free medium with supplements commonly used to culture stem cells gave rise to colonies that varied in their ability to efflux dye and respond to verapamil (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used serum-containing medium because PANC-1 cells most rapidly form large spheres under these conditions. The spheres generated from these cells expressed high mRNA levels of CSC markers, suggesting that they contain CSCs (7,13,(17)(18)(19). A previous study showed that PANC-1 cells grown in a serum-containing medium formed clusters that were heterogeneous for dye efflux, while cells grown in the serum-free medium with supplements commonly used to culture stem cells gave rise to colonies that varied in their ability to efflux dye and respond to verapamil (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter assay, the CSCs of PDAC cells form floating colonies when cultivated in ultra-low-attachment dishes (9)(10)(11) (12). In a previous study, we reported that nestin, a pancreatic CSC marker, is more highly expressed in the spheres of three PDAC cell lines than in nonsphere cells (13). Moreover, pancreatic cancer cells derived from metastatic foci of immunodeficient mice form a greater number of spheres in low-attachment plates than do their primary tumor counterparts (14).…”
Section: Introductionmentioning
confidence: 99%
“…CSCs are niche forming cells enriched with growth factors, and growing them in serum-free conditions containing growth factors, such as epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF), maintains the undifferentiated stem cell state and induces the proliferation of self-renewing, unipotent CSCs from parental cell lines [4, 25, 26]. CSCs are characterised by specific surface markers such as CD133 + /CXCR4 + , CD24 + /CD44 + , CD24 + /CD44 + /ESA + , c-Met + /CD44 + , and ALDH1 + /CD133 + in pancreatic cancer [27, 28]; CD24 −/low /CD44 + in breast cancer; CD44 + in colon/ gastric/ head and neck/ovarian cancer; CD34 + /CD38 − in leukaemia cells; CD13/CD45/CD90 in liver cancer; CD117/CD90/EpCAM in lung cancer; CD20/CD166/Nestin in melanoma cancer; and CD133 + /ABCG2 + in Glioblastoma Multiforme [29, 30]. CSCs also express various markers such as CXCR4/ ESA and Nestin [27].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…CSCs are characterised by specific surface markers such as CD133 + /CXCR4 + , CD24 + /CD44 + , CD24 + /CD44 + /ESA + , c-Met + /CD44 + , and ALDH1 + /CD133 + in pancreatic cancer [27, 28]; CD24 −/low /CD44 + in breast cancer; CD44 + in colon/ gastric/ head and neck/ovarian cancer; CD34 + /CD38 − in leukaemia cells; CD13/CD45/CD90 in liver cancer; CD117/CD90/EpCAM in lung cancer; CD20/CD166/Nestin in melanoma cancer; and CD133 + /ABCG2 + in Glioblastoma Multiforme [29, 30]. CSCs also express various markers such as CXCR4/ ESA and Nestin [27]. CD44 is one of the most important CSC markers for its role in promoting tumour metastasis and invasion.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…However, additional studies revealed that nestin was not a unique marker of neural progenitor/stem cells as the intermediate filament protein was detected in fibroblasts (e.g., heart, kidney), vascular smooth muscle and endothelial cells, pre‐existing cardiomyocytes bordering the peri‐infarct region of the ischemically damaged human/rodent heart, skeletal muscle, and tumorigenic cells (Béguin, Gosselin, Mamarbachi, & Calderone, ; Carlsson, Li, Paulin, & Thornell, ; Chen et al, ; El‐Helou et al, ; Hertig et al, ; Ishiwata et al, ; Meus, Hertig, Villeneuve, Jasmin, & Calderone, Mokry et al, ; Oikawa, Hayashi, Maesawa, Masuda, & Sobue, ; Sejersen & Lendahl, ; Tardif et al, ; Tomioka et al, ; Vaittinen et al, ). Biologically, nestin plays a direct role in the proliferation and migration of normal and tumorigenic cells (Béguin et al, ; Chen et al, ; Liang et al, ; Ishiwata, Matsuda, & Naito, ; Matsuda et al, ; Meus et al, ; Tardif et al, ; Xue & Yuan, ). Three specific regulatory intron regions identified in the nestin gene direct cell‐specific expression of the intermediate filament protein.…”
Section: Introductionmentioning
confidence: 99%